Pengaruh Medication Therapy Management Terhadap Kadar Gula Darah dan Kualitas Hidup Pasien Diabetes Melitus - Devina Jocelin Handoko; Lucia Hendriati; Citra Zita Hermeindita; Teguh Widodo (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia resulting from defects of insulin secretion. Quality of life is an individual's perception of their position in life by having goals, expectations, and standards in life. Medication Therapy Management (MTM) is a program that aims to optimize the therapeutic results. This study aimed to determine the effect of providing MTM services on reducing blood glucose and improving the quality of life of diabetes mellitus patients at North Surabaya Health Center X. This research was conducted by providing questionnaires MMAS-8, SF-36, as well as drug use monitoring sheets. The results were patients with blood glucose category >200 mg/dL, which originally numbered 32 decreased to 16 people. Whereas in control group, it was shown that patients with blood glucose category > 200 mg/dL had a slight decrease from 32 to 26 people. The results of the quality of life of patients in the MTM group showed good quality, which originally numbered 14 increased to 21 people. Whereas in control patients with a good quality of life category, which originally numbered 15 increased to 18 people. The conclusion is MTM services improve the glucose blood level and quality of life MTM patients compared to control patients.